Pensions and Power. The Political and Market Dynamics of Public Pension Plans - Erald Kolasi (Review of Capital as Power, 2022)
This paper uses the theory of `capital as power' to analyze the struggle over public pensions in the United States. While mainstream commentators claim that public pensions must be `reformed' because they are `under funded', I argue that the metrics used to make this argument are unsound. Instead, the push to privatize public pension systems is driven less by actual funding problems, and more by the desires of elite investors who seek to control pension capital and reap the enormous investment fees associated with it. I propose that the deconstruction of public pensions is part of a larger effort to undermine collective action, so as to remove resistance to dominant capital.
Keywords: G2; H55; P16; J3; 330; deregulation; dominant capital; pensions; privatization; public pensions